1999
DOI: 10.1128/jvi.73.6.4536-4542.1999
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Induction of Protective Immunity by a Vaccinia Virus Vector Defective in Late Gene Expression

Abstract: Vaccinia viruses defective in the essential gene coding for the enzyme uracil DNA glycosylase (UDG) do not undergo DNA replication and do not express late genes in wild-type cells. A UDG-deficient vaccinia virus vector carrying the tick-borne encephalitis (TBE) virus prM/E gene, termed vD4-prME, was constructed, and its potential as a vaccine vector was evaluated. High-level expression of the prM/E antigens could be demonstrated in infected complementing cells, and moderate levels were found under noncomplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 33 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…[69][70][71] A replication defective vaccine based on the Lister strain (dVV-L) was created through the deletion of the uracil-DNA-glycosylase (UDG) gene. [72] The resulting vaccine, while replication incompetent outside of certain cell lines which provide exogenous UDG is still capable of initial infection and early gene expression. Early work found that this vaccine candidate had an enhanced safety profile compared to wild-type Lister vaccine.…”
Section: Replication Competent Attenuated Smallpox Vaccinesmentioning
confidence: 99%
“…[69][70][71] A replication defective vaccine based on the Lister strain (dVV-L) was created through the deletion of the uracil-DNA-glycosylase (UDG) gene. [72] The resulting vaccine, while replication incompetent outside of certain cell lines which provide exogenous UDG is still capable of initial infection and early gene expression. Early work found that this vaccine candidate had an enhanced safety profile compared to wild-type Lister vaccine.…”
Section: Replication Competent Attenuated Smallpox Vaccinesmentioning
confidence: 99%
“…The SCV vaccine was generated by targeted deletion of the D13L gene, which encodes an essential viral assembly protein. 18 , 19 This approach to VACV attenuation was chosen, instead of targeting the viral genome replication machinery, 20 to preserve genome amplification, thereby permitting late-phase expression of vaccine antigens from the amplified genomes. Production of SCV vaccines in the SCS line was enabled by the in trans provision of D13 and the host-range protein CP77, which provides VACV multiplication capability in CHO cells.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, immunized mice or mice treated with serum of vaccinated non-human primates were protected against TBEV challenge [ 182 , 193 , 194 ]. Moreover, in situ generation of TBEV VLPs by vaccination of mice with a late-defective recombinant Vaccinia virus (rVACV) encoding for the prM and E proteins, induced VN antibodies and a robust protection upon challenge infection with TBEV [ 195 ]. Altogether, these data suggest that co-expressed prM and E induced superior immune responses with higher protective efficacy than the E protein alone.…”
Section: Novel Approaches and Tbev Target Antigens For The Developmentioning
confidence: 99%